Obedience Pressure and Tax Sanction: An Experimental Study on Tax Compliance - Kadek Pranetha Prananjaya; Niluh Putu Dian Rosalina Handayani Narsa (Jurnal Akuntansi dan Keuangan, 2019)
This research aims to test the influence of tax sanction and obedience pressure on tax compliance. By applying a 2x2 between-subject factorial experiment method, this research has found the empirical evidence that taxpayers tend to be more tax-compliant when the tax sanction is high rather than low. Next, when taxpayers tend to be more non-compliant when they receive obedience pressure from their superior rather than not. Lastly, from the interaction test between tax sanction and obedience pressure variables, the researcher found empirical evidence that shows that, when given high tax sanctions, a taxpayer will have higher tax compliance rate when they do not receive obedience pressure compared with when they receive obedience pressure. This research has a practical implication that obedience pressure from a superior is a key that could potentially reduce tax compliance rate because, although there are low or high sanctions, if there are any obedience pressure, then the tax compliance rate will be low.